2017
DOI: 10.3390/cryst7070184
|View full text |Cite
|
Sign up to set email alerts
|

Photonic Bandgap–Cholesteric Device with Electrical Tunability and Optical Tristability in Its Defect Modes

Abstract: This study proposes a hybrid structure for a one-dimensional (1D) photonic crystal (PC) comprising a tristable cholesteric liquid crystal (CLC) as the defect layer. The CLC exhibits three optically stable states: the Grandjean planar (P), focal conic (FC), and uniform lying helix (ULH) configurations. Specifically, the reflection band of the CLC is set within the photonic bandgap (PBG) of the 1D PC. While the ULH and the FC states can be regarded as the light-on and light-off states for defect-mode peaks in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
(43 reference statements)
1
4
0
Order By: Relevance
“…Besides, in a special case where the frequency of the applied voltage is low enough to bring about electrohydrodynamic instability (EHDI), the ULH state can be obtained in a given voltage region. This phenomenon has been evidenced in some of the early works [17,18,30]. However, when the frequency varies from 1 kHz to 30 Hz in this study, the V-T% curve remains nearly unchanged as shown in Figure 1a.…”
Section: Methodssupporting
confidence: 73%
“…Besides, in a special case where the frequency of the applied voltage is low enough to bring about electrohydrodynamic instability (EHDI), the ULH state can be obtained in a given voltage region. This phenomenon has been evidenced in some of the early works [17,18,30]. However, when the frequency varies from 1 kHz to 30 Hz in this study, the V-T% curve remains nearly unchanged as shown in Figure 1a.…”
Section: Methodssupporting
confidence: 73%
“…That is, when the liquid crystal is cooled from isotropy to the cholesteric Compared with the bistable mode, the tri-stable mode has better display performance and can have multiple switching modes between different optical states in practical applications. However, the ULH texture is a metastable state that is difficult to obtain [40][41][42][43], so various switching methods have been continuously developed [44].…”
Section: Tri-stable Modementioning
confidence: 99%
“…As a result, PC/LC cells have shown promise for a variety of applications. In terms of the optical switchable mechanism based on the stimuli-responsive material properties of LCs through the electrically controlled birefringence effect and other field effects, potential applications of LC-induced defect modes in one-dimensional (1D) hybrid PCs have been suggested, including optically pumped lasers [7,8], filters [9,10], optical switches [11][12][13][14], optical communications [15,16], and beyond. In addition to the use of an applied electric field, the tuning of defect modes can be further fulfilled by dominating their transmission through magnetic fields [17][18][19][20], temperatures [21][22][23], and variations in the angle of incidence of light [24,25].…”
Section: Introductionmentioning
confidence: 99%